Negative electrode material and battery
By controlling the defect structure and surface characteristics of graphite particles, the negative electrode materials that are compared with the volume, comparison surface area and vibration density are prepared, and the diffusion rate and safety of existing graphite negative materials are solved. performance.
Patent Information
- Application Number
- CN202411496498.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-24
AI Technical Summary
The lithium ion diffusion rate of existing graphite negative electrode materials is low, the rate performance is poor, and it is easy to cause lithium-ion separation to cause battery safety problems, which cannot meet high performance needs.
By reasonable control of the overall structure distribution of the flaws such as the surface, pores, and lattice of graphite particles, carbonization and graphization treatment are performed in combination with the proportion and particle size of carbon -based raw materials, pore makers and adhesives to prepare pore volume and comparison surface area And the density density conforms to the negative electrode material of a specific range.
It improves the active sites and diffusion channels for lithium ion deintercalation, improves the rate performance and processing performance of anode materials, and meets the needs of power batteries and energy storage applications.
Smart Images

Figure CN119361702A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application number 202380009569.1, application date June 28, 2023, and invention name "Negative Electrode Materials, Batteries". Technical Field
[0002] The present application belongs to the technical field of negative electrode materials, and more specifically, particularly relates to negative electrode materials and batteries. Background Art
[0003] Graphite-based negative electrode materials have become the most mature negative electrode materials at present due to their wide sources, abundant reserves, relatively stable electrochemical properties, and actual specific capacity density being close to theoretical specific capacity.
[0004] For graphite negative electrode materials, the special layered structure of graphite determines the Li + It can only be embedded from the end face of the material and gradually diffused into the interior of the particles, resulting in a low diffusion rate of lithium ions, poor rate performance, and the negative electrode sheet is more prone to lithium precipitation, resulting in battery short circuit, thermal runaway and other safety issues. Therefore, it is necessary to improve the structure of the graphite material to improve the diffusion channel of lithium ions. It is known to those skilled in the art that the structure of the ideal graphite material is an orderly arrangement of six-membered rings composed of carbon atoms. People generally hope to affect the pore volume and specific surface area of the graphite negative electrode material by adjusting the size of the pores, thereby affecting the electrochemical properties of the graphite material. The pores and cracks on the graphite surface are improved by coating the graphite surface. However, the applicant found that in the actual application process, graphite has different defect structures both macroscopically and microscopically. Simply adjusting the size and structure of the pores has limited improvement in the rate performance of the negative electrode material, and cannot meet people's increasing demand for the performance of graphite materials.
[0005] Therefore, at the current stage when graphite materials have developed to a very mature stage, further research on graphite negative electrode materials is needed to maximize the improvement of graphite's rate performance. Summary of the invention
[0006] In order to overcome the above-mentioned defects, the present application provides a negative electrode material and a battery, which can increase the active sites and diffusion channels for lithium ion deintercalation in the negative electrode material, and is beneficial to improving the rate performance and processing performance of the negative electrode material.
[0007] In a first aspect, an embodiment of the present application provides a negative electrode material, wherein the negative electrode material comprises graphite, wherein the graphite has pores inside and / or on the surface, and the pore volume of the negative electrode material is V cm 3 / kg, specific surface area is S m 2 / g and a tap density of T g / cc, the negative electrode material satisfies: 2≤V*S / T≤10;
[0008] The pore volume was measured using the ASAP2460 equipment of the American Micromeritics Company and the BJH Desorption cumulative volume of pores model. Calculated within the aperture range;
[0009] The pore volume of the negative electrode material is 2 cm 3 / kg~6cm 3 / kg; the specific surface area of the negative electrode material is 1.0m 2 / g~2.0m 2 / g; the tap density of the negative electrode material is 0.85g / cc to 1.40g / cc.
[0010] In some embodiments, the particle size of the negative electrode material satisfies the following relationship: 0.9≤(D90-D10) / D50≤1.8.
[0011] In some embodiments, D50 of the negative electrode material is 10 μm to 20 μm.
[0012] In some embodiments, D90 of the negative electrode material is 25 μm to 36 μm.
[0013] In some embodiments, D10 of the negative electrode material is 7 μm to 9 μm.
[0014] In some embodiments, the pores include at least one of micropores and mesopores.
[0015] In some embodiments, the specific capacity of the negative electrode material is 330 mAh / g to 370 mAh / g.
[0016] In some embodiments, the average pore size of the pores is
[0017] In some embodiments, the negative electrode material satisfies: 2.5≤V*S / T≤8.4.
[0018] In a second aspect, an embodiment of the present application provides a battery, wherein the battery comprises the negative electrode material described in the first aspect.
[0019] The technical solution of this application has at least the following beneficial effects:
[0020] It is known to those skilled in the art that the pore volume of artificial graphite within a certain range can increase the Li +The diffusion channel of the negative electrode material and the specific surface area within a certain range can ensure sufficient electrochemical reaction interface, promote the diffusion of lithium ions at the solid-liquid interface and in the solid phase, reduce concentration polarization, and help improve the capacity and rate performance of the negative electrode material. On this basis, the applicant has conducted in-depth research and found that the comprehensive performance of the negative electrode material may not be optimal and stable if only sufficient pore volume and specific surface area are met. Graphite as a negative electrode material not only needs to rely on pores and surface structures to provide sufficient diffusion channels and reaction interfaces for lithium ion deintercalation to obtain excellent electrochemical performance, but also requires the pole piece to have good processing performance, so that the battery can achieve a relatively ideal energy density and keep the pole piece stable during the cycle. The applicant believes that the pores, particle surfaces, crystal planes and other structures that destroy the arrangement of the graphite hexagonal rings can be considered as defects of the ideal graphite structure and exist in the graphite particles. Therefore, by reasonably controlling the defects, not only will the performance of the graphite material not be reduced, but the electrical properties of the material can also be improved to a certain extent. In order to obtain the optimal graphite defect structure, it is necessary to accurately adjust the overall structural distribution of defects such as the surface, pores, and lattice of graphite particles. Through analysis, it is believed that this application combines the three factors of pore volume, specific surface area, and tap density of graphite materials to conduct a large number of experimental explorations, and control the V*S / T of the negative electrode material within the range of 2 to 10. This means that the negative electrode material can fully utilize the advantages of the rich overall structural defects of the material itself to increase the lithium ion diffusion rate on the basis of ensuring the processing performance, and ultimately achieve the purpose of improving the high-rate charge and discharge performance of artificial graphite negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0022] Figure 1 This is a SEM image of the negative electrode material prepared in Example 8 of the present application, magnified 1000 times. DETAILED DESCRIPTION
[0023] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0024] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0026] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0027] For graphite negative electrode materials, graphite materials need to be prepared into slurry and further coated on copper foil current collector during use, and maintain a good electrode structure during long cycles, so graphite negative electrode materials are required to have good processing performance; at the same time, because lithium ions can only enter the graphite interlayer from the end face during the lithium extraction process, the diffusion channel is limited, which restricts the diffusion of lithium ions at the solid-liquid interface and in the solid phase, further limiting the high-rate charge and discharge performance of graphite. Generally speaking, artificial graphite has a certain number of pore structures. On the one hand, the presence of pores can increase the Li + The diffusion channel inside the graphite material reduces the Li + The diffusion resistance of the material can be reduced, thereby effectively improving the rate performance of the material. On the other hand, too many pore structures will lead to an excessively large specific surface area of the material, which not only reduces the volume density of the graphite, but also causes the pores on the surface to make the surface of the graphite particles more uneven and rough, and the fluidity of the graphite particles is poor, which ultimately causes the tap density of the graphite material to decrease, thereby leading to the deterioration of the product processing performance and electrochemical properties such as the first effect and cycle. In fact, simply improving the pore structure does not achieve the best comprehensive performance of graphite negative electrode materials, and there is still a lot of room for improvement. Most researchers stay at the exploration of the influence of a single factor on the performance of graphite materials, and have not conducted in-depth research from the perspective of the synergy between multiple factors to maximize the improvement of the rate performance of graphite.
[0028] Therefore, at the current stage when graphite materials have developed to a very mature stage, simply improving one parameter can no longer meet the market demand for low-cost, high-performance graphite materials. It is necessary to explore the mechanism of the coordinated action of multiple factors and develop graphite negative electrode materials that meet market demand.
[0029] The following is a detailed description of one of the preparation processes developed by the applicant as an example to further illustrate the preparation process and related products.
[0030] The present invention provides a method for preparing a negative electrode material, comprising the following steps:
[0031] S10. Mix the carbon-based raw material, the pore-forming agent and the binder to obtain a first precursor, wherein the particle size of the pore-forming agent satisfies 0.5≤(D90-D10) / D50≤0.8, and 5nm≤D50≤8nm, and the mass ratio of the carbon-based raw material, the pore-forming agent and the binder is (70-94):(1-10):(5-20).
[0032] S20, subjecting the first precursor to a first heat treatment to carbonize it, thereby obtaining a second precursor.
[0033] S30. Perform a second heat treatment on the second precursor to graphitize it and obtain a negative electrode material, wherein the second heat treatment includes: first heating the temperature to 1600°C to 1800°C at a heating rate of 2°C / min to 5°C / min, then heating the temperature to 3000°C to 3200°C at a heating rate of 2°C / min to 8°C / min, and keeping the temperature for 6h to 10h. After keeping the temperature, cool the temperature to 800°C at a cooling rate of 0.1°C / min to 0.5°C / min, and finally cool the temperature to room temperature at a cooling rate of 2°C / min to 4°C / min.
[0034] In the above scheme, the present application mixes carbon-based raw materials in appropriate proportions, pore formers and binders of specific particle sizes and particle size distributions, and then carbonizes and graphitizes them. The pore formers are uniformly and quickly removed by controlling the heating rate, cooling rate and graphitization holding time of the carbonization and graphitization processes, creating more lithium ion diffusion channels inside the graphite material, achieving the purpose of regulating the defect structure and surface morphology of the graphite negative electrode material, optimizing the tap density, pores and specific surface area parameters of the graphite negative electrode material, and finally effectively improving the processing performance and rate performance of the graphite negative electrode material. The process method is simple and the production cost is low. The obtained graphite negative electrode material has the characteristics of high tap density, good processing performance and excellent rate performance, which can meet the use needs of power battery and energy storage customers.
[0035] The preparation method of the present application is described in detail below:
[0036] Step S10, mixing the carbon-based raw material, the pore-forming agent and the binder to obtain a first precursor, wherein the particle size of the pore-forming agent satisfies 0.5≤(D90-D10) / D50≤0.8, and 5nm≤D50≤8nm, and the mass ratio of the carbon-based raw material, the pore-forming agent and the binder is (70-94):(1-10):(5-20).
[0037] In some embodiments, the carbon-based raw material needs to be shaped before mixing with the carbon-based raw material, the pore former and the binder to obtain a carbon-based raw material with a specific particle size.
[0038] In some embodiments, the particle size of the carbon-based raw material after shaping treatment is 10μm to 25μm, specifically 10μm, 12μm, 15μm, 18μm, 20μm, 22μm or 25μm, etc., and of course it can also be other values within the above range, which is not limited in this application.
[0039] In some embodiments, the carbon-based feedstock includes at least one of petroleum coke, needle coke, pitch coke, and isotropic coke.
[0040] In some embodiments, the pore former includes at least one of silicon oxide and silicon carbide.
[0041] In some embodiments, the particle size of the pore former satisfies 0.5≤(D90-D10) / D50≤0.8, and 5nm≤D50≤8nm. Specifically, the value of (D90-D10) / D50 can be 0.5, 0.6, 0.7 or 0.8, etc., and of course it can also be other values within the above range, which is not limited in this application. The median particle size D50 of the pore former can be 5nm, 6nm, 7nm or 8nm, etc., and of course it can also be other values within the above range, which is not limited in this application. Within the above-mentioned limited range, it shows that the pore former has a smaller and more concentrated particle size, which is conducive to the uniform and rapid escape of the pore former from the carbon-based raw material during the graphitization process, and the formation of a uniform and controllable pore defect structure in the final graphite negative electrode material as a channel for lithium ion diffusion.
[0042] In some embodiments, the binder includes at least one of coal tar, petroleum tar, petroleum resin, phenolic resin, epoxy resin, coumarone resin, and furan resin.
[0043] In some embodiments, the mass ratio of the carbon-based raw material, the pore former and the binder is (70-94): (1-10): (5-20). Specifically, the mass ratio of the carbon-based raw material, the pore former and the binder can be 70:10:20, 75:8:17, 80:5:15, 85:3:12 or 94:1:5, etc. Of course, it can also be other values within the above range, and the present application is not limited here. If the amount of the pore former added is greater than the specified range of the present application, it is easy to cause an increase in the specific surface area of the material, and at the same time cause the tap density of the graphite material to decrease, thereby causing the product processing performance, the first efficiency and the cycle and other electrochemical properties to deteriorate; if the amount of the pore former added is less than the specified range of the present application, the pore structure formed is too small, and the purpose of creating more lithium ion diffusion channels and electrochemical reaction interfaces for the negative electrode material cannot be achieved. At the same time, during the graphitization process, the pore former is equivalent to an impurity in the carbon raw material, which may affect the crystallization of graphite polycrystals, and then affect the distribution of lattice and crystal surface defects of the graphite material. It can be understood that when the amount of binder added is less than the specified range of this application (the mass ratio of carbon-based raw materials to binders is greater than 94:5), the obtained artificial graphite is mainly primary particles, and when the proportion of the binder is higher (the mass ratio of carbon-based raw materials to binders is less than or equal to 85:12), the obtained artificial graphite is mainly secondary particles.
[0044] S20, subjecting the first precursor to a first heat treatment to carbonize it, thereby obtaining a second precursor.
[0045] In some embodiments, the temperature of the first heat treatment is 800°C to 1100°C. Specifically, the temperature of the first heat treatment can be, for example, 800°C, 900°C, 1000°C or 1100°C, etc. Of course, it can also be other values within the above range, and the present application is not limited thereto.
[0046] In some embodiments, the holding time of the first heat treatment is 4 h to 10 h, specifically 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., and of course, it can also be other values within the above range, which is not limited in this application.
[0047] In some embodiments, the heating rate of the first heat treatment is 2°C / min to 10°C / min, specifically 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc., and of course it can also be other values within the above range, which is not limited in this application.
[0048] In some embodiments, the cooling rate after the first heat treatment is 1°C / min to 5°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, etc. Of course, it can also be other values within the above range, which is not limited in this application.
[0049] In some embodiments, the first heat treatment is performed under a protective atmosphere including at least one of nitrogen, helium, neon, argon, krypton, and xenon.
[0050] During the first heat treatment process, the carbon-based raw material in the first precursor undergoes pyrolysis and shrinkage to be converted into a carbon solid with microcrystalline arrangement. The organic molecules and impurities present in the carbon-based raw material, pore-forming agent and binder slowly escape during the heating process to form a pore structure. In the first precursor of the pore-forming agent with a specific particle size, by controlling the temperature, time and heating rate of the first heat treatment, pores and surfaces with a specific structural distribution are formed in the carbon solid, forming uniformly distributed structural defects that are beneficial to the diffusion of lithium ions, thereby providing excellent reaction raw materials for the subsequent second heat treatment graphitization.
[0051] S30. Perform a second heat treatment on the second precursor to graphitize it, wherein the second heat treatment includes: heating the second precursor to 1600°C to 1800°C within 6h to 10h, with a heating rate of 2°C / min to 5°C / min; heating to 3000°C to 3200°C within 4h to 6h, with a heating rate of 2°C / min to 8°C / min; keeping the temperature for 6h to 10h, and cooling to 800°C after 150h to 200h, with a cooling rate of 0.1°C / min to 0.5°C / min; and then cooling to room temperature within 4h to 6h, with a cooling rate of 2°C / min to 4°C / min, to obtain a negative electrode material.
[0052] Controlling the heating rate, cooling rate and holding time of the second heat treatment within the above range is beneficial for the second precursor to evenly and quickly decompose and escape the pore-forming agent from the material during the graphitization process, thereby creating more lithium ion diffusion channels inside the graphite material. In addition, the graphite crystal structure is mostly polycrystalline, and there are crystal plane defects between the grain boundaries. At the same time, the above control can also maintain a highly regular crystal structure, thereby achieving the purpose of regulating the structure and morphology of the graphite negative electrode, optimizing the product's tap density, pores and specific surface area parameters, and improving the processing performance and rate performance of the negative electrode material.
[0053] Those skilled in the art will understand that the above-described method for preparing the battery is only an example, and other methods commonly used in the art may be used without departing from the contents disclosed in the present application.
[0054] The present application provides a negative electrode material, the negative electrode material includes graphite, the graphite has pores inside and / or on the surface, and the pore volume V (cm 3 / kg), specific surface area S (m 2 / g) and tap density T (g / cc) satisfy: 2≤V*S / T≤10;
[0055] The pore volume was measured using the ASAP2460 equipment from Micromeritics, USA, and the BJH Desorption cumulative volume of pores model was used. Calculated within the aperture range.
[0056] In the above scheme, the negative electrode material provided by the present application is produced and processed by adding a binder and a pore-forming agent of a specific particle size to a carbon-based raw material, and then carbonizing and graphitizing the heating process through a specific heating rate and a cooling rate, so that the pore-forming agent forms specific pores inside and / or on the surface of the graphite, and the distribution of the pores can reflect the defect structure distribution in the graphite polycrystal to a certain extent, because there is a specific pore structure distribution inside the material after graphitization, and these pore structure defects are mainly caused by the volatilization of organic matter, pore-forming agent, carbon source pyrolysis shrinkage and polycrystalline orientation. Different internal stresses and other phenomena eventually make the inside / surface of the graphite present closed pores, open pores, interlayer microcracks and pores, etc., so as to achieve precise control of defects inside and / or on the surface of the graphite, so that the material pore volume, specific surface area and tap density reach the ideal control design requirements. Among them, evenly distributed pore defects are formed inside and / or on the surface of the graphite, and evenly distributed pores can reduce the expansion of the graphite negative electrode material during the charge and discharge process. And the pore defects can be used as additional lithium storage space to increase the lithium storage capacity of the negative electrode material, while causing an increase in the specific surface area. When the negative electrode material is made into an electrode and applied to a battery, after the electrolyte is injected, the pores inside the artificial graphite particles are filled with the electrolyte. During charging and discharging, an electrochemical reaction occurs inside the electrode. The pore defects on the surface and inside of the graphite particles and the outer surface of the graphite particles exposed due to uneven force at the defects create more lithium ion diffusion channels and electrochemical reaction interfaces for the negative electrode material at a suitable tap density, which can promote the diffusion of lithium ions at the solid-liquid interface and in the solid phase, reduce concentration polarization, and help improve the capacity and rate performance of the negative electrode material. In addition, the negative electrode material of the present application has good processing performance, can prevent the graphite sheets of the graphite negative electrode material from falling off during the cycle, and is conducive to improving the cycle performance of the material.
[0057] Generally speaking, the pore volume within a certain range in graphite can increase the diffusion channel of Li ions, and the specific surface area within a certain range can ensure sufficient electrochemical reaction interface, promote the diffusion of lithium ions at the solid-liquid interface and in the solid phase, reduce concentration polarization, and help improve the capacity and rate performance of the negative electrode material. However, the chaotic distribution of material pores and the increase in specific surface area limit the improvement of the rate performance and processing performance of graphite negative electrode materials. Therefore, improving the pore structure alone cannot make the graphite negative electrode material have the best and most stable electrochemical performance. Therefore, the present application is beneficial to obtain a negative electrode material with better comprehensive performance such as rate performance and cycle performance on the basis of maintaining good processing performance by controlling the V*S / T of the graphite negative electrode material within the above range. In the present application, the value range of V*S / T is 2 to 10, and specifically can be 2, 2.5, 3, 3.6, 4, 4.5, 5, 5.3, 6, 6.7, 7, 7.3, 8, 8.4, 9, 9.5 or 10, etc., of course, it can also be other values within the above range, and the present application is not limited here. In the above formula, V is the pore volume of the graphite material, S is the specific surface area of the graphite material, and T is the tap density of the graphite material. The larger V is, the richer the pore structure of the graphite particles is, and the larger the specific surface area S is within a certain range. However, it will cause the first efficiency of the graphite negative electrode material to be lower and the cycle performance to be worse; the smaller T is, the processing performance of graphite as a negative electrode material in the process of preparing slurry and electrode will deteriorate, that is, it is impossible to improve the rate performance and processing performance of the graphite negative electrode material through a single factor, and controlling a single factor has limited improvement on the rate performance of the material. Therefore, the present application uses the V*S / T combined parameter to combine the above two factors, and believes that although the pores formed by closed pores cannot be accurately measured, they can still provide abundant channels for lithium ions. Due to the effect of defect stress, microcracks are easily generated around the closed pores and at the grain boundaries, which are potential sources of fracture inside the material. When the graphite particles are broken, they will be hit and broken preferentially at the positions where the defect stress is large and there are microcracks. At this time, the closed pores inside will be opened and exposed on the surface, or the deep pores inside the open pores will be exposed to form the outer surface of the graphite particles. After the surface is formed, the surface of the material is finally made rough; at the same time, some grain boundary defects of graphite polycrystals may also be split and exposed under stress, while their surfaces are relatively smooth. Therefore, the combined state of the above two surface defects will affect the fluidity of graphite particles. Finally, the applicant found that the relationship between tapping, specific surface area and pore volume can be used to reflect the comprehensive structural state of graphite internal / surface defects to a certain extent, and V*S / T can be controlled in the range of 2 to 10, so as to obtain better rate performance and processing performance at the same time. Preferably, the value range of V*S / T is 2.5 to 8.4.
[0058] In some embodiments, the particle size of the negative electrode material satisfies the following relationship: 0.9≤(D90-D10) / D50≤1.8, and 10μm≤D50≤20μm. In the above formula, D90 is the particle size at which the cumulative distribution of material particles is 90%, D10 is the particle size at which the cumulative distribution of material particles is 10%, and D50 is the particle size at which the cumulative distribution of material particles is 50%, also known as the median particle size.
[0059] Ideal battery materials need to have a narrow particle size distribution. Studies have shown that too much fine powder will cause the overly active battery material to continue to consume electrolyte during circulation, resulting in deterioration of capacity retention rate, while large particles with greater expansion are prone to particle pulverization during circulation, which easily leads to continuous thickening of SEI. Therefore, by narrowing the particle size distribution, the cycle performance of the material can be improved. In the negative electrode material of the present application, (D90-D10) / D50 is between 0.9 and 1.8, and D50 is between 10μm and 20μm, indicating that the particle size span of the negative electrode material is small, that is, the negative electrode material has a relatively uniform particle size distribution, so that the material can avoid the above problems while further having a higher packing density, which is convenient for improving the electrochemical performance of the negative electrode material. Specifically, the value of (D90-D10) / D50 can be 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.8, etc., and of course it can also be other values within the above range, which is not limited in this application. If (D90-D10) / D50 is less than 0.9, it indicates that the particle size distribution of the negative electrode material is too narrow, which is not conducive to the coating of the negative electrode material for preparing the pole piece, resulting in poor processing performance; if (D90-D10) / D50 is greater than 1.8, it indicates that there are more fine powders in the negative electrode material, which is not conducive to the improvement of the cycle performance of the negative electrode material.
[0060] In some embodiments, the median particle size D50 of the negative electrode material can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm, etc., and of course it can also be other values within the above range, which is not limited in this application.
[0061] In some embodiments, D90 of the negative electrode material is 25 μm to 36 μm, specifically 25 μm, 28 μm, 30 μm, 32 μm, 35 μm or 36 μm, etc. Of course, it can also be other values within the above range, which is not limited in this application.
[0062] In some embodiments, D10 of the negative electrode material is 7 μm to 9 μm, specifically 7 μm, 7.5 μm, 8 μm, 8.5 μm or 9 μm, etc. Of course, it can also be other values within the above range, which is not limited in the present application.
[0063] In some embodiments, the pore volume of the negative electrode material is 2 cm 3 / kg~6cm 3 / kg, specifically, the pore volume of the negative electrode material is 2cm 3 / kg、3cm 3 / kg, 4cm 3 / kg、5cm 3 / kg or 6cm 3 / kg, etc., and of course, it can also be other values within the above range, which is not limited in this application. Within the above range, it is shown that the graphite negative electrode material has a more suitable pore structure, which can effectively provide sufficient channels for the diffusion of lithium ions, which is beneficial to improving the rate performance of the negative electrode material.
[0064] In some embodiments, the specific surface area of the negative electrode material is 1.0 m 2 / g~2.0m 2 / g, specifically, the specific surface area of the negative electrode material can be 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g or 2.0m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited in this application. Within the above range, the negative electrode material has abundant surface active sites, which is also conducive to improving the rate performance of the material.
[0065] In some embodiments, the tap density of the negative electrode material is 0.85 g / cc to 1.40 g / cc. Specifically, the tap density of the negative electrode material can be 0.85 g / cc, 1.0 g / cc, 1.10 g / cc, 1.20 g / cc, 1.30 g / cc or 1.40 g / cc, etc. Of course, it can also be other values within the above range, and this application is not limited here. Within the above range, it shows that the negative electrode material has good processing performance, which reduces the difficulty of pole piece coating and battery production, and is also conducive to maintaining the structural stability of the pole piece during the cycle process, improving the material's cycle performance and the battery's energy density.
[0066] In some embodiments, the specific capacity of the negative electrode material is 330 mAh / g to 370 mAh / g. Specifically, the specific capacity of the negative electrode material may be 330 mAh / g, 340 mAh / g, 350 mAh / g, 360 mAh / g or 370 mAh / g, etc. Of course, it may also be other values within the above range, which is not limited in this application.
[0067] In some embodiments, the pores include at least one of micropores and mesopores.
[0068] In some embodiments, the average pore size is Specifically it can be or Of course, it can also be other values within the above range, which is not limited in this application.
[0069] An embodiment of the present application also provides a battery, which includes the above-mentioned negative electrode material.
[0070] Those skilled in the art will understand that the above-described method for preparing the battery is only an example. Without departing from the contents disclosed in the present application, other methods commonly used in the art may be used, and other types of batteries may be prepared for testing, such as sodium ion batteries, potassium ion batteries, etc.
[0071] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments. Within the scope of the unchanged main rights, appropriate changes can be made to the implementation.
[0072] Example 1
[0073] (1) The petroleum coke raw material is crushed, and the median particle size of the crushed material powder is less than 20 μm.
[0074] (2) The powder obtained in step (1), the nano-silicon oxide pore-forming agent and the coal tar binder are uniformly mixed to obtain a first precursor, wherein the mass ratio of petroleum coke, the pore-forming agent and the binder is controlled to be 70:10:20, the D50 of the pore-forming agent is 8 nm, and (D90-D10) / D50=0.5;
[0075] (3) carbonizing the first precursor obtained in step (2) under heating conditions of 1000° C. to obtain a second precursor;
[0076] (4) The second precursor obtained in step (3) was graphitized at 3000°C, and the temperature rise and fall process curve was controlled as follows: the temperature was raised to 1800°C within 10 hours (the heating rate was 3°C / min), the temperature was raised to 3000°C within 6 hours (the heating rate was 3.3°C / min), and the temperature was kept for 6 hours. After the temperature was kept, the temperature was lowered to 800°C after 150 hours (the cooling rate was 0.3°C / min), and then the temperature was lowered to room temperature within 6 hours (the cooling rate was 2.2°C / min);
[0077] (5) The material obtained in step (4) is crushed, screened, and mixed to finally obtain a graphite negative electrode material with a D50 of 10 μm to 20 μm.
[0078] The negative electrode material comprises primary artificial graphite particles and secondary artificial graphite particles, and the secondary artificial graphite particles are mainly used. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0079] Example 2
[0080] Different from Example 1, the heating and cooling curve used in step (4) is as follows: heating to 1800°C within 8 hours (heating rate of 3.8°C / min), heating to 3000°C within 5 hours (heating rate of 4°C / min), keeping warm for 8 hours, cooling to 800°C after 170 hours (cooling rate of 0.2°C / min), and then cooling to room temperature within 5 hours (cooling rate of 2.7°C / min) to obtain a graphite negative electrode material.
[0081] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, mainly secondary artificial graphite particles. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0082] Example 3
[0083] Different from Example 1, the heating and cooling curve used in step (4) is as follows: heating to 1800°C within 6 hours (heating rate of 5°C / min), heating to 3200°C within 5 hours (heating rate of 4.7°C / min), keeping warm for 10 hours, cooling to 800°C after 190 hours (cooling rate of 0.2°C / min), and then cooling to room temperature within 4 hours (cooling rate of 3.3°C / min) to obtain a graphite negative electrode material.
[0084] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, mainly secondary artificial graphite particles. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0085] Example 4
[0086] Different from Example 1, the heating and cooling curve used in step (4) is as follows: heating to 1600°C within 6 hours (heating rate of 4.4°C / min), heating to 3200°C within 4 hours (heating rate of 6.7°C / min), keeping warm for 10 hours, cooling to 800°C after 200 hours (cooling rate of 0.2°C / min), and then cooling to room temperature within 4 hours (cooling rate of 3.3°C / min) to obtain a graphite negative electrode material.
[0087] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, mainly secondary artificial graphite particles. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0088] Example 5
[0089] Different from Example 1, in step (2), the mass ratio of petroleum coke, pore former and binder is 80:5:15.
[0090] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, mainly secondary artificial graphite particles. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0091] Example 6
[0092] Different from Example 1, in step (2), the mass ratio of petroleum coke, pore former and binder is 85:3:12.
[0093] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, mainly secondary artificial graphite particles. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0094] Example 7
[0095] Different from Example 1, in step (2), the mass ratio of petroleum coke, pore former and binder is 90:2:8.
[0096] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, mainly secondary artificial graphite particles. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0097] Example 8
[0098] Different from Example 1, in step (2), the mass ratio of petroleum coke, pore former and binder is 94:1:5.
[0099] In this embodiment, the negative electrode material includes primary artificial graphite particles and secondary artificial graphite particles, such as Figure 1As shown, it is a SEM image of the negative electrode material prepared in this embodiment. Figure 1 It can be seen that the particle size of artificial graphite is relatively small, and it is mainly composed of primary particles of artificial graphite. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0100] Example 9
[0101] Different from Example 1, the D50 of the pore-forming agent in step (2) is 5 nm, and (D90-D10) / D50=0.7.
[0102] The negative electrode material comprises primary artificial graphite particles and secondary artificial graphite particles, and the secondary artificial graphite particles are mainly used. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0103] Example 10
[0104] Different from Example 1, the D50 of the pore-forming agent in step (2) is 6 nm, and (D90-D10) / D50=0.5.
[0105] The negative electrode material comprises primary artificial graphite particles and secondary artificial graphite particles, and the secondary artificial graphite particles are mainly used. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0106] Embodiment 11
[0107] Different from Example 1, the carbonization temperature in step (3) is 800°C.
[0108] The negative electrode material comprises primary artificial graphite particles and secondary artificial graphite particles, and the secondary artificial graphite particles are mainly used. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0109] Example 12
[0110] Different from Example 1, the carbonization temperature in step (3) is 1100°C.
[0111] The negative electrode material comprises primary artificial graphite particles and secondary artificial graphite particles, and the secondary artificial graphite particles are mainly used. The values of the pore volume, tap density and specific surface area of the negative electrode material are shown in Table 1.
[0112] Comparative Example 1
[0113] Different from Example 1, in step (2), the mass ratio of petroleum coke, pore former and binder is 65:23:12.
[0114] Comparative Example 2
[0115] Different from Example 1, no pore former is added in step (2), and the mass ratio of petroleum coke to binder is 94:6.
[0116] Comparative Example 3
[0117] Different from Example 1, the particle size of the pore-forming agent in step (2) is D50=15 nm, (D90-D10) / D50=1.5.
[0118] Comparative Example 4
[0119] Different from Example 1, the D50 of the pore-forming agent in step (2) is 3 nm, and (D90-D10) / D50=0.4.
[0120] Comparative Example 5
[0121] The difference from Example 1 is that in step (4): the second precursor obtained in step (3) is graphitized at a high temperature of 3000°C, and the temperature rise and fall process curve is controlled as follows: the temperature is raised to 1800°C within 17 hours (the temperature rise rate is 1.76°C / min), the temperature is raised to 3000°C within 6 hours (the temperature rise rate is 3.3°C / min), and the temperature is kept for 6 hours. After the temperature is kept, the temperature is lowered to room temperature (the temperature lowering rate is 2.2°C / min).
[0122] Comparative Example 6
[0123] Different from Comparative Example 1, in step (4): the second precursor obtained in step (3) is graphitized at a high temperature of 3000°C, and the temperature rise and fall process curve is controlled as follows: the temperature is raised to 3000°C within 17 hours (the heating rate is 3°C / min), kept at this temperature for 6 hours, and then cooled to room temperature (the cooling rate is 3°C / min) after keeping at this temperature.
[0124] Performance Testing
[0125] (1) Testing method for median particle size of negative electrode materials:
[0126] The particle size distribution range of the negative electrode material was tested by Malvern laser particle size analyzer.
[0127] (2) Testing methods for pore volume and average pore diameter of negative electrode materials:
[0128] The test was carried out using the ASAP2460 equipment from Micromeritics, USA. The pore volume V and average pore diameter were calculated using the BJHDesorption cumulative volume of pores model. Calculated within the aperture range.
[0129] (3) Testing method for specific surface area of negative electrode materials:
[0130] The dynamic specific surface area rapid determination instrument JW-DX of Beijing Jingwei Gaobo Science and Technology Co., Ltd. was used for testing. The unit is m 2 / g.
[0131] (4) Test method for the tap density of negative electrode materials:
[0132] The tap density T is tested using a Quantachrome tap density analyzer Dual Autotap produced by Anton Paar (Shanghai) Trading Co., Ltd. The tap density T is a value after 222 vibrations, in units of g / cc.
[0133] (5) The surface morphology of the negative electrode material was observed using a Hitachi S4800 scanning electron microscope.
[0134] (6) Battery performance test method: The samples prepared in Examples 1 to 20 and Comparative Examples 1 to 2: the mass ratio of conductive glue (CMC+SP): SBR = 95:1.5:1.5:2 were magnetically stirred in deionized water for 8 hours to make them evenly mixed. The mixed slurry was coated on copper foil and vacuum dried at 60°C as a working electrode. Metal lithium was used as the counter electrode and reference electrode, the diaphragm was Celgard2325, the electrolyte was 1 mol·L-1LiPF6-EC (ethylene carbonate) / DMC (dimethyl carbonate) / EMC (ethyl methyl carbonate) (volume ratio of 1:1:1), and the CR2016 button battery was assembled in a glove box filled with high-purity argon gas, and 4 batteries were prepared for each group of samples.
[0135] The first discharge capacity / first discharge efficiency test was carried out on a LAND battery tester, and the charge and discharge conditions were as follows: standing for 2 hours; discharge: 0.1C to 0.005V, 0.09C, 0.08C…0.02C to 0.001V; standing for 15 minutes; charge: 0.1C to 1.5V; standing for 15 minutes.
[0136] The expansion test after 20 cycles of full charge was measured using a mold battery, and the surface density of the graphite negative electrode was 70g / m 2 The compacted density is 1.6g / cc, the positive electrode is LCO, and the surface density is 166g / m 2 , the compaction density is 3.5-3.7g / cc; the cycle test conditions are 0.1C charge and discharge rate for one week in the first week, 0.2C charge and discharge rate for one week in the second week, and 0.5C charge and discharge rate from the 3rd to the 20th week. Then, the electrode thickness change data collected by the sensor during the cycle process is matched with the cycle data collected by the electrochemical test cabinet to obtain the 20-week full-charge expansion value.
[0137] Table 1. Parameter test results of negative electrode materials of various embodiments and comparative examples
[0138]
[0139] Table 2. Performance parameter measurement results of negative electrode materials of various embodiments and comparative examples
[0140]
[0141]
[0142] As shown in Tables 1 and 2, the present application can reflect the overall distribution of defects such as pores, lattices, and interlayer microcracks inside graphite particles through the ratio of the specific surface area, pore volume, and tap density of the constructed negative electrode material. Within the limited range of 2≤V*S / T≤10, it is shown that when the negative electrode material of the present application is made into an electrode and applied to a battery, the pore defects inside the negative electrode material are evenly distributed, and the evenly distributed pore defects can reduce the expansion of the graphite negative electrode material during the charging and discharging process, and the pores can be used as additional lithium storage space to increase the lithium storage capacity of the negative electrode material. At the same time, the specific surface area is increased within a certain range, so that when the negative electrode material is made into an electrode and applied to a battery, after the electrolyte is injected, the pores inside the artificial graphite particles are filled with the electrolyte. During charging and discharging, electrochemical reactions occur inside the electrode, and the defects create more lithium ion diffusion channels and electrochemical reaction interfaces for the negative electrode material, which can promote the diffusion of lithium ions at the solid-liquid interface and in the solid phase, reduce concentration polarization, and help improve the capacity and rate performance of the negative electrode material. In addition, the appropriate surface roughness also enables the negative electrode material of the present application to have better processing performance, which can prevent the graphite sheets of the graphite negative electrode material from falling off during the cycle process, and is beneficial to improving the cycle performance of the material.
[0143] In Comparative Example 1, too much pore-forming agent is added, which leads to structural defects in the negative electrode material, and the surface fluidity is worse, resulting in a lower tap density of the negative electrode material, and ultimately causing the processing performance of the negative electrode material to deteriorate, which increases the difficulty of electrode coating and battery manufacturing. It is also not conducive to maintaining the structural stability of the electrode during the cycle process, and is not conducive to improving the cycle performance of the material and the energy density of the battery.
[0144] In Comparative Example 2, no pore former is added, resulting in insufficient pore structure of the negative electrode material. The limited diffusion channels will restrict the diffusion of lithium ions at the solid-liquid interface and in the solid phase, further limiting the high-rate charge and discharge performance of graphite.
[0145] The particle size of the pore-forming agent used in Comparative Example 3 does not meet the specified range of the present application, resulting in excessively large pore sizes in some of the prepared negative electrode materials, uneven distribution of pore defects in the graphite material, and lower tap density of the negative electrode material, which ultimately causes its processing performance to deteriorate, increasing the difficulty of electrode coating and battery manufacturing. It is also not conducive to maintaining the structural stability of the electrode during the cycle, and is not conducive to improving the cycle performance of the material and the energy density of the battery.
[0146] The median particle size of the pore-forming agent used in Comparative Example 4 is smaller than the range specified in the present application, which makes the pore size and pore volume of the prepared artificial graphite too small. The limited diffusion channels will limit the diffusion of lithium ions at the solid-liquid interface and in the solid phase, further limiting the high-rate charge and discharge performance of the graphite.
[0147] The parameters of the graphitization treatment and / or the addition ratio of the pore-forming agent in Comparative Examples 5 and 6 are not within the specified range of the present application. Although the pore volume V, specific surface area S and tap density T of the finally prepared negative electrode material are respectively within the numerical range of the implementation mode of the present application, the value of V*S / T does not satisfy the range of 2 to 10, which makes the rate performance, first effect and cycle performance of the negative electrode material worse than those of the negative electrode material prepared in the examples of the present application.
[0148] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises graphite, the graphite has pores inside and / or on the surface, and the pore volume of the negative electrode material is V cm 3 / kg, specific surface area is Sm 2 / g and a tap density of Tg / cc, and the negative electrode material satisfies: 2≤V*S / T≤10; The pore volume was measured using the ASAP2460 equipment of the American Micromeritics Company and the BJH Desorption cumulative volume of pores model. Calculated within the aperture range; The pore volume of the negative electrode material is 2 cm 3 / kg~6cm 3 / kg; the specific surface area of the negative electrode material is 1.0m 2 / g~2.0m 2 / g; the tap density of the negative electrode material is 0.85g / cc to 1.40g / cc.
2. The negative electrode material according to claim 1, characterized in that The particle size of the negative electrode material satisfies the following relationship: 0.9≤(D90-D10) / D50≤1.
8.
3. The negative electrode material according to claim 1, characterized in that The D50 of the negative electrode material is 10 μm to 20 μm.
4. The negative electrode material according to claim 2, characterized in that The D90 of the negative electrode material is 25 μm to 36 μm.
5. The negative electrode material according to claim 2, characterized in that The D10 of the negative electrode material is 7 μm to 9 μm.
6. The negative electrode material according to claim 1, characterized in that The pores include at least one of micropores and mesopores.
7. The negative electrode material according to claim 1, characterized in that The specific capacity of the negative electrode material is 330 mAh / g to 370 mAh / g.
8. The negative electrode material according to claim 1, characterized in that The average pore size of the pores is 9. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies: 2.5≤V*S / T≤8.
4.
10. A battery, characterized in that: The battery comprises the negative electrode material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Long-life natural graphite cathode material and preparation method thereof
CN110828824A
Negative electrode material and battery
CN115881952A
Negative electrode material and battery
CN115954472A
Negative electrode material and battery
CN116057734A
Cited By
Lithium oxide preparation method, system and equipment
CN120069230A